TURISMO SOSTENIBLE COMO FACTOR DE DESARROLLO EN EL CANTÓN QUEVEDO, AÑO 2022 - Yum On Villanueva, Yomira Lisbeth (2022)
This research focuses on "analyzing sustainable tourism as a factor of development in the Canton Quevedo in the year 2022", and it is carried out due to the erroneous management of natural resources when designing a tourist place. Emphasizing that entrepreneurs They do not have the correct guidelines to benefit from their projects with materials found in nature. The city of Quevedo is the economic and productive center of the province of Los Ríos since it is geographically located on the road to reach many places in Ecuador. But that is what we want to transform so that this city is more than a commercial or leisure meeting point, but is it a place visited by tourists? Is it an option to go on vacation and visit its tourist attractions? To develop this research work, the research method was used, a survey was carried out on a certain number of people residing in the city and several entrepreneurs in the tourism sector were also surveyed. A quantitative and type explanation was carried out to determine the real problem that tourism in Quevedo presents, applying observation and interview techniques through declaratory tools and photographs that will serve as evidence for the research work.